Ideas and scientific concepts in the personalities of the Ukrainian and Polish language frontier: Professor Mikhailo Lesiv - Shevchenko, Larysa (Current issues of Ukrainian linguistics: theory and practice, 2018)
The article is devoted to the analysis of the perspective of the idea and scientific concept of the Ukrainian and Polish language frontier, which is considered by the author as an intellectual cultural and geographical area that generates the diffusion of languages, cultures, and lifestyles. Sociocultural relations, which are formed historically, are expressed in different forms of culture. Language reflects the influences of other languages, enriching them with new linguistic units, influencing various levels of expression of specific forms of words. In the article, the problem of the Ukrainian and Polish language frontier is considered with a projection on the range of scientific interests of the Polish professor, Mykhailo Lesiv. The researcher consistently worked out the scientific concept of the positive influence on the development of the languages of the Ukrainian-Polish borderlands, considering the concrete impacts of grammar, phonetics, onomastics, and the development of the stylistic potential of the Polish and Ukrainian languages. The idea of Mikhail Lesiv about the influence not only of the Polish language on Ukrainian but also of the Ukrainian language in Polish in the cultural-linguistic boundary is important for understanding the perspective of the concept. The author of the article states that this view is promising because it allows us to speak about the mutual enrichment of languages, cultural entropy of peoples, united by good neighborliness. Conceptual ideas of Mykhailo Lesiv are argued by numerous publications (over 1,000 publications), in which the factual characteristics of the language frontier are investigated. The historical development of the Ukrainian language from the point of view of M. Lesiv is considered. Different forms and different languages, its functional potential in written culture and dialectal environment are analyzed. It is noted, in particular, on the onomastic intelligence of Mikhail Lesiv, the possibilities of their deployment in modern studies on the development of literary languages. The cultural heritage of Mykhailo Lesiv detailed, substantiates the actual material of the concept of the cultural space of the Ukrainian-Polish language frontier, building the prospect of linguistic contacts and good-neighborliness of the two Slavic nations.
Keywords: Ukrainian-Polish language frontier, civilization unity of Slavdom, a cultural history of nations, Mykhailo Lesiv, Ukrainian language, Polish language, scientific concept of mutual enrichment of the Ukrainian-Polish language frontier.